Anticoagulant Kinetics Following Bolus Injection of Heparin - Mockros, Lyle F; Hirsch, Samuel D; Zuckerman, Leon; Caprini, Joseph A; Robinson, William P; Vagher, J Paul (Thrombosis and Haemostasis, 1979)
Bolus injections of beef-lung heparin at doses of 50, 100 and 200 u/kg body weight were administered to mongrel dogs. Neutralization of the anticoagulant effect was evaluated using sequential samples withdrawn from the animals (in vivo samples) and aliquots from a 100 ml sample withdrawn from the dog at 30 minutes post-injection (in vitro samples). Tests of the activated partial thromboplastin time (APTT) and prothrombin time (PT) did not indicate the degree of anticoagulation. Tests of the whole blood clotting time (WBCT), celite- activated whole blood clotting time (ACT), and celite-activated thromboelastography (ATEG) indicated pronounced hypocoagulability immediately after the injection, followed by a fairly rapid decay in anticoagulability, and a slight Ziype/coagulability at three to four hours post injection. The results from the in vitro ATEG samples were essentially identical to those on the in vivo samples, whereas the in vitro WBCT and ACT generally indicated higher degrees of anticoagulation. Calculated half-lives of the anticoagulant effect are significantly shorter than previously reported, being 18 to 36 minutes, and slightly dose dependent. The decay of the effects, however, does not appear to follow a single exponential curve, dropping very rapidly immediately post-injection and at a somewhat slower rate 60 or more minutes post-injection.